Limitations to Indigenous Peoples Participation in the Arctic Council - Esther Jónsdóttir 1996- (2020)
For decades indigenous peoples have used various platforms to represent themselves as self-determining peoples with specific rights and interests. For the indigenous peoples in the Arctic, the Arctic Council is a platform to do so. The forum is unique because it provides Arctic indigenous organizations a specific role as permanent participants which means they have full participation rights and full consultation rights at all Arctic Council activities. However, the current framework of the forum limits these rights and creates a gap between the member states and the permanent participants. This is because the permanent participants struggle to keep up with the workload and to take on leadership roles in the forum because they do not have the resources that the member states have. This gives the member states an advantage because they have greater opportunities to represent themselves and influence decision-making processes. The member states also have the opportunity to control the agenda through the chairmanship and can veto decisions made by the Arctic Council. Changes need to be made to the framework of the forum if it is to address these challenges that the permanent participants face but currently measures are not being taken. This is because the Arctic states and the Arctic Council are based on state-centric ideas regarding state sovereignty and operate in IR based on Westphalian ideology. For the member states the current framework benefits them because they have the most power of the actors in the Arctic Council and the permanent participants have to rely on them to get their point across. Frumbyggjaþjóðir hafa í áratugi nýtt sér ýmiskonar vettvang til þess að koma réttindum sínum og hagsmunum á framfæri sem þjóðir með sjálfsákvörðunartökurétt. Fyrir frumbyggjaþjóðir á norðurslóðum er Norðurskautsráð vettvangurinn til þess. Norðurskautsráð er einstakur vettvangur að því leytinu til að samtök frumbyggja á norðurslóðum eiga sæti í ráðinu sem ‚varanlegir þátttakendur‘ (Permanent Participants) og hafa ...